The Impact of Perceived Threat of Pandemic Upon the Employee Retention in The Public and Private Hospitals - ALI, MARYAM; BILAL KAYANI, MUHAMMAD; SARWAT, RABIA; IDREES, SABA (The journal of contemporary issues in business and government, 2021)
The study was conducted to evaluate the impact of perceived threat of COVID-19 upon the retention of doctors of twin cities'' hospitals of Pakistan. Two moderator’s compensation and training and development were assessed as moderating the relationship between perceived threat of COVID-19 and employee retention. The model is tested on healthcare sector of Pakistan and the data was collected by the doctors of twin cities of Pakistan. A sample of 208 doctors was collected using random sampling technique. Sem-PLS software was used to analyze the statistics. Perceived Threat of COVID-19 have a positive significant impact on employee’s retention whereas compensation is negatively and significantly moderating the relationship between perceived threat of COVID-19 and employee retention. Training and development are insignificantly moderating the relationship between perceived threat of COVID-19 and employee retention. Doctors were found to be not intended to leave their hospitals in threat of COVID-19. Compensation was found to moderate the relation between the both variables, such that weakening the relationship. Training and development were found to be ineffective as a moderator in the relation of perceived threat of COVID-19 and employee retention.